2015
DOI: 10.1017/s1368980015001044
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’ awareness and use of menu labels in eating establishments: results from a focus group study

Abstract: Objective: Menu labelling has been identified as a potential strategy to help individuals make healthier choices when eating out. Although adolescents eat out often, little research involving menu labelling has been conducted with this population. The objectives of the present study were to: (i) gather qualitative information from adolescents regarding use of menu labels when eating out; (ii) gather adolescents' suggestions for optimal ways to design menu labels; and (iii) examine differences between adolescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 53 publications
(74 reference statements)
2
18
0
Order By: Relevance
“…Unlike other types of food labelling, PACE labelling has the potential to serve as a continual reminder to the public about the importance of participating in regular physical activity to ensure good energy balance. There is also observational evidence that the public prefer PACE food labelling over other types of food labelling 12…”
Section: Introductionmentioning
confidence: 99%
“…Unlike other types of food labelling, PACE labelling has the potential to serve as a continual reminder to the public about the importance of participating in regular physical activity to ensure good energy balance. There is also observational evidence that the public prefer PACE food labelling over other types of food labelling 12…”
Section: Introductionmentioning
confidence: 99%
“…Socioeconomic status determined the type of school and educational resources available to the adolescents as well. This factor alone was the greatest predictor of food choices in all studies (Evans et al, 2016).…”
Section: Resultsmentioning
confidence: 91%
“…Results showed that PACE labels have statistically significant effects on consumers' preferences for both products in this study. It has also been demonstrated that the public prefer PACE labels over other types of food labels [69].…”
Section: Discussionmentioning
confidence: 99%